Conserved chemical properties of young humic acid fractions in tropical lowland soil under intensive irrigated rice cropping - OLK; CASSMAN; MAHIEU; RANDALL (Wiley, 1998)
Increasing cropping intensity (i.e. number of crops per year) of irrigated rice seems to cause an accumulation of phenolic compounds in the soil organic matter (SOM). We have studied the chemical nature of SOM in a broad range of soil types at different sites with long‐term double‐ and triple‐crop irrigated rice trials. Accumulation of phenols, as measured by 13C nuclear magnetic resonance spectroscopy, was found in both the mobile humic acid (MHA) and calcium humate (CaHA) fractions at all sites, regardless of soil type, hydrology during the fallow, and with and without inorganic fertilizer or green manures. Although phenols accumulated consistently in MHA and CaHA, the C, N and hydrolysable amino acid concentrations, degree of humification and amounts of MHA and CaHA were significantly altered by crop management, and they varied from site to site. Our results are consistent with the hypothesis that the accumulation of phenols is a characteristic of the anaerobic, or nearly anaerobic, soil conditions that exist at the initial stages of SOM formation in submerged irrigated rice soils. By contrast, other SOM properties are additionally influenced by soil conditions that govern the degradation and turnover of existing SOM. The chemical properties of MHA and CaHA indicated that they are labile, and the quantities of these HA fractions were more sensitive to recent management than were total soil C or N.